Penyuluhan Hukum tentang Kreatifitas Siswa Sekolah Sebagai Content Creator pada Media Sosial Ditinjau dari Hukum Bisnis di Madrasah Aliyah Negeri (MAN ) 13 Jakarta Selatan - Atmoko, Dwi; Noviriska; Baihaki, Ahmad; M. Hutagalung, Jantarda; Nainggolan, Indra Lorenly; Siswanto, Heru; Sugeng (Abdi Bhara, 2025)
The development of digitalization is something that has become a necessity in all levels of society and all fields of activity, including education. The use of technology for society is used to support activities. The dependence of society on the use of social media, through various social media tools such as Facebook, Instagram, Twitter, Tik Tok and others, opens up new job opportunities related to technology and digitalization. Digitalization allows for wider relationships, so it is often used in the fields of marketing and production. Social media is a platform that allows its users to create, share, and participate in content. In this case, there is a need for legal recognition through counseling related to protection for content creator business actors. The increase in the use of social media by students then opens up new opportunities in pursuing a profession in the digital era, one of which is becoming a Content Creator. The content created is not only useful for the fields of production and marketing, but can also be useful for Education, where students can use it in relation to learning and Education. Content creation in the layman's view is considered easy, but in fact it is not, because a content creator needs to think about engagement, awareness, personal branding. With this understanding, it is necessary for students of MAN 13 South Jakarta to get an introduction to becoming a content creator and how to get legal protection in running the business, so that they do not experience obstacles in starting to create content.